Clinical Pearls in Anaesthesia for Endoscopic Endonasal Transsphenoid Pituitary Macroadenoma Surgery - Shah Shagun B; Kulkarni Anita (The Indian Anaesthetists' Forum, 2015)
Endoscopic Endonasal Trans-sphenoid Surgery (EETS) aided by avant-garde neuro-navigation techniques, ultrasonic aspirators and bone curettes has come of age. Endoscopic surgery supersedes conventional microscopic approach due to better visualization, avoidance of craniotomy, brain retraction and undue neurovascular manipulation with less morbidity, blood loss and improved safety. Anaesthetic techniques must be tailored to cater for such advances in surgery.